The Potential of Nutrigenomics from Viewpoint of Animal Nutrition: A Mini Review - Bimrew Asmare (South Valley University, 2019)
Nutrigenomics is relatively new area of science which requires more appraisal and further research. Therefore, it must be well understood before it is applied in the field of agriculture particularly in animal science. From earlier few studies, it has been learnt that nutrigenomics and allied sciences have significant importance to serve as modern tool fornutritional research in comprehending the problems related to animal production and health. But the level of awareness is not that much raised for maximum exploitation of the science. For this reason, efforts have to be exerted to uncover the state of current knowledge, skill and practices how nutrigenomics helps in boosting animal productivity and health condition. One of the approaches to expand this knowledge is using various dissemination mechanisms such as bringing together the information from different sources, analyzing and interpreting. In scientific or research language, this is referred as review. To this end, literature and articles related to animal nutrition and health which were produced over several years are browsed and reviewed. Based on the review, it is possible to recognize that the future of animal nutrition requires intensified feeding and precise nutrient specification of animals. Hence, understanding the importance of nutrigenomics, exploring how it works, and identifying what benefit it has is the scope of the review. This piece of paper is therefore written to describe what nutrigenomics mean, its importance, how it can be applied and what contribution it has to the field of animal sciences.